Effects of calorie restriction with n-3 long-chain polyunsaturated fatty acids on metabolic syndrome severity in obese subjects: A randomize-controlled trial. (December 2015) - Lee, Hsiu-Chuan; Cheng, Wen-Yi; Hsu, Yi-Hao; Su, Hsiu-Yueh; Huang, Brian E. T.-G.; Lin, Yen-Kuang; Chan, Wing P.; Su, Chien-Tien; Huang, Shih-Yi
Highlights: All groups had significant reduction in waist circumference, blood pressure, and other cardiometabolic parameters. The MetS severity decreased significantly post-intervention and correlated with the serum IL-6 level and n-6/n-3 ratio. Calorie-restricted conditions improved cardiometabolic parameters, including circulating fatty acid profile and IL-6 level. No adverse effects of LC-PUFA and meal replacement treatments were observed. Abstract: Metabolic syndrome (MetS) increases the risk of type 2 DM and cardiovascular disease. We here evaluated the effects of a calorie-restriction diet with 2.13 g/day n-3 long-chain polyunsaturated fatty acid supplementation in MetS patients. The 188 participants were randomly assigned one of four calorie-restriction diets for 12 weeks: calorie-restriction (n = 44), calorie-restriction meal replacement (n = 45), calorie-restriction with fish oil (n = 44), or calorie-restriction meal replacement with fish oil (n = 44); 179 participants completed the trial. After treatment, all groups had significant reduction in waist circumference, blood pressure, and cardiometabolic parameters. Results indicate that long-chain polyunsaturated fatty acid (LC-PUFA) supplementation under calorie-restriction exert beneficial effects on metabolic parameters.